Health-Related Disinformation, Fact-Checkers, and Hoaxes: The Case of Vaccines - Sánchez-Gey Valenzuela, Nuria; Gomes-Gonçalves, Sónia; Jiménez-Marín, Gloria (Revista Española de Comunicación en Salud, 2026)
Introduction: Misinformation, although inherent in the history of human communication, has taken on particular significance with the expansion of digital technologies and social media, affecting the health sector. Objective: To identify and categorise the most common vaccine-related hoaxes to understand their potential social and informational effects. Methodology: A quantitative, exploratory and descriptive study was conducted by analysing fact-checks of false content about vaccines carried out by the Spanish fact-checking organisations Maldita.es and Newtral. Results: The main hoaxes focus on alleged adverse effects and the false composition of vaccines. Furthermore, they frequently rely on testimonials from figures perceived as authorities to bolster the credibility of the false information and foster attitudes of rejection towards vaccination. Conclusion: Misinformation about vaccines poses a threat to public health by influencing social perceptions and individual decision-making. It is therefore essential to strengthen media literacy and promote communication strategies grounded in scientific evidence to mitigate its impact.
Keywords: Communication; Misinformation; Fact-checking; Health; Vaccines; Verification